An Analysis of Power Relations in Kanae Minato’s Novel Confessions (2008) - Ninna febrianna Sejahterawati (Passage, 2019)
This study which is entitled An Analysis of Power Relations in Kanae Minato’s Novel Confession (2008) aims to find and investigate the how power is exercised in Kanae Minato’s novel Confessions. Using Foucault’s theory of power, this study is expected to analyze the writer’s purposes of constructed power relations in the novel. Focusing on how power is exercised, the data is expected to be found by analyzing the novel using qualitative research design with descriptive nature. After the data is collected, this study aims to analyze the meaning of exercised power in the novel. This qualitative research analyzes the data by the form of words, phrases and sentences. Keywords: Power Relation, Foucault